Development of rapid and precise approach for quantification of bacterial taxa correlated with soil health - Abdelmoneim, Taghreed Khaled; Mohamed, Mahmoud S. M.; Abdelhamid, Ismail Abdelshafy; Wahdan, Sara Fareed Mohamed; Atia, Mohamed A. M. (Frontiers in Microbiology, 2023)
The structure and dynamic of soil bacterial community play a crucial role in soil health and plant productivity. However, there is a gap in studying the un-/or reclaimed soil bacteriome and its impact on future plant performance. The 16S metagenomic analysis is expensive and utilize sophisticated pipelines, making it unfavorable for researchers. Here, we aim to perform 1) in silico and in vitro validation of taxon-specific qPCR primer-panel in the detection of the soil beneficial bacterial community, to ensure its specificity and precision, and 2) multidimensional analysis of three soils/locations in Egypt ('Q', 'B', and 'G' soils) in terms of their physicochemical properties, bacteriome composition, and wheat productivity as a model crop. The in silico results disclosed that almost all tested primers showed high specificity/precision toward the target taxa. Among seventeen measured soil properties, the electrical conductivity (EC) value (up to 5 dS/m) of 'Q' soil provided an efficient indicator for soil health among the tested soils. The 16S NGS analysis showed that the soil bacteriome significantly drives future plant performance, especially the abundance of Proteobacteria and Actinobacteria as key indicators. The functional prediction analysis results disclosed a high percentage of N-fixing bacterial taxa in 'Q' soil compared to other soils, which reflects their positive impact on wheat productivity. The taxon-specific qPCR primer-panel results revealed a precise quantification of the targeted taxa compared to the 16S NGS analysis. Moreover, twelve agro-morphological parameters were determined for grown wheat plants, and their results showed a high yield in the 'Q' soil compared to other soils; this could be attributed to the increased abundance of Proteobacteria and Actinobacteria, high enrichment in nutrients (N and K), or increased EC/nutrient availability. Ultimately, the potential use of a taxon-specific qPCR primer-panel as an alternative approach to NGS provides a cheaper, user-friendly setup with high accuracy.